Pro Grunt.js - Cryer, James; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Pro Grunt.js gets you quickly up-to-speed with this popular JavaScript-based task runner. Author James Cryer takes you from initial installation all the way through to authoring successful plugins. Using hands-on examples you will learn about CSS linting, combination, compilation and minification; JavaScript linting, AMD modules, and templates; image processing and optimizing; and creating a local server. You will then move on to more advanced topics such as LiveReload, Test Automation, Modular configuration, and combining tasks. Finally you will see how to scaffold plugins using Grunt init and Yeoman, how to test them with Mocha and Chai, and how to publish them so others can use them. Start using Grunt.js to improve your workflows by using Pro Grunt.js today.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems